Clinical Concepts on Thyroid Emergencies - Papi, Giampaolo; Corsello, Salvatore Maria; Pontecorvi, Alfredo (Frontiers in Endocrinology, 2014)
Objective. Thyroid-related emergencies are caused by overt dysfunction of the gland that are so severe that require admission to intensive care units frequently. Nonetheless, in the ICU setting, it is crucial to differentiate patients with non-thyroidal illness and alterations in thyroid function tests from those with intrinsic thyroid disease. This review presents and discusses the main etiopathogenetical and clinical aspects of hypothyroid coma (HC) and thyrotoxic storm (TS), including therapeutic strategy flow-charts. Furthermore, a special chapter is dedicated to the approach to massive goiter, which represents a surgical thyroid emergency. Data source. We searched the electronic MEDLINE database to September 2013. Data selection and Data extraction. Reviews, original articles and case reports on “myxedematous coma”, “hypothyroid coma”, “thyroid storm”, “thyrotoxic storm”, “massive goiter, “huge goiter”, “prevalence”, “etiology”, “diagnosis”, “therapy”, “prognosis” were selected. Data synthesis and conclusions. Severe excess or defect of thyroid hormone are rare conditions which jeopardize the life of patients in most cases. Both HC and TS are triggered by precipitating factors, which occur in patients with severe hypothyroidism or thyrotoxicosis, respectively. The pillars of HC therapy are: high dose l-thyroxine and/or tri-iodothyroinine; i.v. glucocorticoids; treatment of hydro-electrolyte imbalance (mainly, hyponatraemia); treatment of hypothermia; not rarely, endotracheal intubation and assisted mechanic ventilation are needed. Therapy of TS is based on beta-blockers, thyrostatics, and i.v. glucocorticoids; eventually, high-dose iodide compounds or lithium carbonate may be of benefit. Surgery represents the gold standard treatment in patients with euthyroid massive nodular goiter, although new techniques – e.g., percutaneous laser ablation - are helpful in subjects at high surgical risk or refusing operation.